A SUPPLIER DISCOVERY FRAMEWORK FOR EFFECTIVE AND EFFICIENT CONFIGURATION OF A SUPPLY CHAIN - Lee, Choonghyun; Lee, Young Hoon; Jeong, Buhwan; Cho, Hyunbo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
A supplier registry can play a central role in configuring a global supply chain for service-oriented enterprise integration by providing an open platform for publishing and discovering suppliers distributed over Internet. The availability of correct classification schemes used to organize suppliers based on their capability descriptions is the key to building an effective registry. This paper discusses the clustering-based construction of classification schemes from existing capability descriptions of suppliers and then the registration and retrieval of suppliers based on these classification schemes. This approach is based on the use of similarity measures to discriminate any two suppliers’ capability descriptions. The results look promising in that small medium suppliers can expose themselves to the large companies in an efficient manner, while large companies can diversify their supply sources.